(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Prosthetics of dentition defects in patients with diabetes mellitus has many nuances and involves the selection of orthopedic designs considering microangiopathy, hyposalivation, hyperglycemia, and a decrease in the rate of regenerative and reparative processes. Orthopedic treatment using dentures with lock fasteners is aimed at eliminating traumatic occlusion and articulation, redistributing masticatory pressure, and restoring dentition defects. Dentures made from any material used in prosthetics with lock fasteners are installed in cases of partial tooth loss, excessive tooth wear, impaired chewing function, pathological bite, pronounced maxillary lumps, and are also indicated for patients with a flat palate, periodontal diseases, and various other comorbidities.